DENGUE KNOWLEDGE IN INDOOR DENGUE PATIENTS FROM LOW SOCIOECONOMIC CLASS; ETIOLOGY, SYMPTOMS, MODE OF TRANSMISSION AND PREVENTION - Shams, Nadia; Amjad, Sadia; Yousaf, Nadeem; Ahmed, Waqar; Kumar Seetani, Naresh; Farhat, Shazia (Journal of Ayub Medical College Abbottabad, 2018)
Background: Dengue fever has emerged as an emerging public health issue during last decade bearing significant morbidity and economic burden particularly in third world countries. Current study aims to assess various domains of knowledge of indoor dengue patients. Methods: This descriptive cross-sectional study was conducted at Medicine dept. Rawal Institute of Health Sciences Islamabad and BBH Rawalpindi over 6 months. One hundred & twenty-five adult indoor confirmed cases of dengue from lower socioeconomic class were included after ethical approval. The 25-item dengue knowledge questionnaire including aetiology, symptoms, modes of transmission and prevention of dengue was filled. Results: Among 125 cases (77% males and 23% females), mean age was 30±13 years. Mean knowledge score was 11±5 points; with excellent knowledge in 6%, good knowledge (22%), moderate knowledge (23%), fair knowledge (34%) and poor knowledge (17%). Mosquito being a vector of dengue was identified by 78%, with peak time in afternoon (48%). Symptoms identified include fever (95%), headache (55%), muscle pain (44%), rash (33%), retro-orbital pain (32%), joint pains (28%) and abdominal pain (18%). Flies and ticks aren’t the vectors of dengue according to 61% and 74% respectively, special mosquito is vector (54%), i.e., Aedes Aegypti (18%) that breeds in standing water (53%). Preventive measures identified were netting (56%), insecticide sprays (54%), covering water containers (38%), removing standing water (36%), mosquito repellents (17%), cutting down bushes (22%) and pouring chemicals in standing water (18%). Conclusion: Our patients from lower socioeconomic class, though aware of vector and mode of transmission, have insufficient knowledge of prevention and vector control measures. There is need to strengthen dengue awareness through community based programs, social media, schools and health care centres for high risk people well before the expected epidemic season about mode of transmission, vector control, screening and early approach to health care facility. Keywords: Dengue fever; Dengue Knowledge; Dengue Prevention